RELIGIUSITAS TOKOH UTAMA DALAM NOVEL OUR SECRET KARYA KAK NANA - Utari Utari; Elsa Mulya Karlina (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study aims to reveal the forms and values ​​of religiosity displayed by the main character in the novel Our Secret by Kak Nana. The main character in this novel lives in a pesantren environment and is depicted as having a strong religious character, which is reflected in his attitude, actions, and way of dealing with life's conflicts. This study uses a descriptive qualitative approach with a library method, and uses the theory of religiosity from Glock and Stark which includes five dimensions: belief, worship practices, religious experiences, religious knowledge, and the application of religious values ​​in life. The results of the analysis show that the main character shows religiosity through sensitivity to worship times, surrender to destiny, sincerity in praying, and commitment to preaching through a cultural approach. In addition, the character also shows moral and social values ​​such as patience, empathy, and responsibility towards others. These findings show that religiosity in literary works is not only present in symbolic form, but also real through the actions and life choices of the characters, making this novel a reflective medium for readers to understand the meaning of religiosity in everyday life.